2015
DOI: 10.1002/ejoc.201501178
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Access to Polyfunctionalized 3,4‐Dihydroquinazolinones through a Sequential N‐Acyliminium Ion Mannich Reaction Cascade

Abstract: A microwave‐promoted one‐pot, three‐component sequential cyclization‐Mannich reaction of unactivated ketones, o‐formyl carbamates and primary amines has been developed. Cyclic N‐acyliminium ions are generated in situ from the carbamate and amine starting materials. This metal‐free cascade protocol provides rapid access to structurally diverse 3,4‐dihydroquinazolinones in good to excellent yields with high regioselectivity for the terminal methyl group, in the case of unsymmetrical methyl alkyl ketones. Key fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…For example, Wang et al (2009) reported the synthesis of 4-alkyl-2(1H)-quinazolinones via the cyclization of 1-(2-alkynyl-phenyl)ureas catalyzed by TfOH and Saunthwal et al (2015) described a green and catalyst-free straightforward tandem synthesis of functionalized tetrahydroquinazolines from 2-aminophenylacrylate. Sawant et al (2015) developed a microwave-promoted sequential cyclization-Mannich reaction of ketones, o -formyl carbamates and primary amines to form polyfunctionalized 3,4-dihydroquinazolinones. Fukamachi et al (2010) described a selective construction of 3,4-dihydroquinazoline-2-thiones by reacting 3-(2-isothiocyanatophenyl)propanoic derivatives with primary amines.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Wang et al (2009) reported the synthesis of 4-alkyl-2(1H)-quinazolinones via the cyclization of 1-(2-alkynyl-phenyl)ureas catalyzed by TfOH and Saunthwal et al (2015) described a green and catalyst-free straightforward tandem synthesis of functionalized tetrahydroquinazolines from 2-aminophenylacrylate. Sawant et al (2015) developed a microwave-promoted sequential cyclization-Mannich reaction of ketones, o -formyl carbamates and primary amines to form polyfunctionalized 3,4-dihydroquinazolinones. Fukamachi et al (2010) described a selective construction of 3,4-dihydroquinazoline-2-thiones by reacting 3-(2-isothiocyanatophenyl)propanoic derivatives with primary amines.…”
Section: Introductionmentioning
confidence: 99%
“…Zhu et al 9 described an efficient synthesis of 4-alkyl-2(1H)-quinazolinones by cyclization of 1-(2-alkynyl-phenyl)ureas catalyzed by TfOH. More recently Odell et al 10 published a rapid access to polyfunctionalized 3,4-dihydroquinazolinones through a sequential N-acyliminium ion Mannich reaction cascade.…”
Section: Introductionmentioning
confidence: 99%
“…We believe that this study improves the chemical applicability of the venerable N ‐acyliminium ions, and also provides a better understanding of their catalytic reactivity with weak nucleophiles. The potential of the fascinating and easily available Sn(NTf 2 ) 4 Lewis superacid catalyst is also broadened, and we hope that the specific and general information gained from this study will be useful to the scientific community …”
Section: Resultsmentioning
confidence: 97%